Application of New Integral Transform for Ordinary Differential Equation with Unknown Initial Conditions - Neamah ALbukhttar, Athraa; Abdulmohdi, Fatimah; Neamah Kadhim, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The Shehu transform fundamental properties were shown by Shehu. In this paper, we extended application of Shehu transform to solve ordinary differential where initial conditions known or unknown and formulas of general solutions of some ordinary differential equations are achieved